Development of Health Enhancement Lifestyle Profile - Taiwanese Short Form Version (HELP-T-SF) for the community-dwelling elderly - Pei-Chi Su; Hui-Fen Mao; Wen-Chen Cheng (PLoS ONE, 2025)
Background The Health Enhancement Lifestyle Profile - Taiwan Version (HELP-T) assesses the lifestyle profiles of the older adults through participation in activities across seven domains: exercise, diet, social and productive activities, leisure, activities of daily living, stress management and spiritual participation, and other health behaviors. This study aimed to develop a short form of HELP-T (HELP-T-SF) to reduce assessment time and evaluate its psychometric properties. Methods This three-phase study comprised item reduction using archival data (2012–2013), field testing (n = 223; 2023), and psychometric evaluation (n = 117; 2024) among community-dwelling older adults. Data collection included the HELP-T-SF, original HELP-T, WHO-5 Well-Being Index, and quality-of-life questions. Analysis employed classical test theory. Results The finalized HELP-T-SF, consisting of 20 items. Internal consistency for the total score was Cronbach’s α = 0.78 (95% CI: 0.54 to 0.89); test–retest reliability over 7–14 days was ICC (3,1) = 0.78 (95% CI: 0.54 to 0.89); correlation with the long form was r = 0.75 (95% CI: 0.56 to 0.86). Convergent validity showed moderate correlations with well-being and quality of life. The short form reduced assessment time to 10–15 minutes. Conclusions The HELP-T-SF is a valid tool for assessing lifestyle profiles in community-dwelling older adults, assisting practitioners in lifestyle medicine for understanding older adults’s lifestyle profile, setting client-centered goals and designing personalized lifestyle interventions.